Design and implementation of real-time multi-sensor vision systems - Popovic, Vladan (Springer, 2017)
This book discusses the design of multi-camera systems and their application to fields such as the virtual reality, gaming, film industry, medicine, automotive industry, drones, etc. The authors cover the basics of image formation, algorithms for stitching a panoramic image from multiple cameras, and multiple real-time hardware system architectures, in order to have panoramic videos. Several specific applications of multi-camera systems are presented, such as depth estimation, high dynamic range imaging, and medical imaging.
Keywords: Image processing.; Multisensor data fusion.; Computer vision.; elektronické knihy; electronic books